2013
DOI: 10.1175/jas-d-12-0173.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Geographic Asymmetry of Typhoon Translation Speed across the Mountainous Island of Taiwan

Abstract: This paper examines the effect of topographically phase-locked convection on the motion of typhoons across the island of Taiwan. Data for 84 typhoons that reached Taiwan’s eastern coast from 1960 to 2010 are analyzed, with motions compared to the long-term average overland translation speed. For 61 continuous-track typhoons among all cases, 77% of the slow-moving tropical cyclones (TCs) made landfall on the northern end of Taiwan’s eastern coast, while 60% of the fast storms had southeastern coastal landfalls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 32 publications
(30 reference statements)
7
100
0
Order By: Relevance
“…Note that in the present study, we found that the vorticity tendency (VT) approach is appropriate since the TC track is consistent with the VT, similar to that applied to TC motion, such as northwestward beta drift (e.g., Holland, 1983) and shear effects (e.g., Wu and Emanuel, 1993). The PV Tendency (PVT) diagnostic approach, as originally proposed by Wu and Wang (2000) and Chan et al (2002) and applied to real-case simulations (e.g., Hsu et al, 2013;Chan, 2013, 2014;Wang et al, 2013), appears to be an attractive method and will be considered in our future research. …”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Note that in the present study, we found that the vorticity tendency (VT) approach is appropriate since the TC track is consistent with the VT, similar to that applied to TC motion, such as northwestward beta drift (e.g., Holland, 1983) and shear effects (e.g., Wu and Emanuel, 1993). The PV Tendency (PVT) diagnostic approach, as originally proposed by Wu and Wang (2000) and Chan et al (2002) and applied to real-case simulations (e.g., Hsu et al, 2013;Chan, 2013, 2014;Wang et al, 2013), appears to be an attractive method and will be considered in our future research. …”
Section: Discussionsupporting
confidence: 59%
“…Due to complicated interactions between orographic and thermal forcing, both idealized numerical simulations (e.g., Chang, 1982;Bender et al, 1987;Yeh and Elsberry, 1993a,b;Lin et al, 1999Lin et al, , 2005, denoted as L05 hereafter, Lin and Savage, 2011;Chan, 2013, 2014;Wu et al, 2015), real-case simulations (e.g., Wu, 2001;Lin et al, 2006;Jian and Wu, 2008;Huang et al, 2011;Hsu et al, 2013;Wang et al, 2013;Wu et al, 2015), and observations (Brand and Blelloch, 1974;Wang, 1980;Hsu et al, 2013) have shown that when a typhoon approaches Taiwan's CMR, its track may deflect either to the north or south upstream of the mountain. It has been proposed that the track deflection may be due to mean cyclonic circulation (e.g., Chang, 1982;Bender et al, 1987), channeling mechanism (e.g., Lin et al, 1999;Jian and Wu, 2008;Huang et al, 2011), blocking effect (e.g., Elsberry, 1993a,b, L05, Lin andSavage, 2011), latent heating (e.g., Hsu et al, 2013;Chan, 2013, 2014;Wang et al, 2013), terrain-induced gyes Chan, 2013, 2014), approaching angle and landing location (Lin and Savage, 2011;Tang and Chan, 2014), and midtropospheric northerly asymmetric flow (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting finding of the study is that the contribution of diabatic heating becomes important for irregular tropical cyclone motion, suggesting that track oscillations as well as irregular track changes may be explained by changes in the convection pattern. The PVT approach has been used in understanding tropical cyclone motion in the presence of the effects of land surface friction (FR), river deltas, coastal lines, mountains, islands, cloud-radiative processes and sea surface pressure gradients (e.g., Wong and Chan, 2006;Yu et al, 2007;Fovell et al, 2010;Hsu et al, 2013;Wang et al, 2013;Choi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%